Living apart together– public-private cooperation in the field of financial crime. - Meerts, Clarissa A.; Huisman, Wim; Kleemans, Edward R. (Crime, Law & Social Change, 2025)
The focus of this paper consists of the extent to which public-private cooperation and relationships exists between law enforcement actors and private (corporate) investigators in the field of internal financial crime within corporations, and which factors may be identified that hinder or advance cooperation. Only limited public-private cooperation seems to exist. Rather, public-private relationships move on a scale ranging from more to less contact, both in intensity and in longevity. Promoting factors that are identified consist of the importance of mutual interests, shared goals and focus, networking and trust, the dedicated individual and communication and expectation management. Impeding factors include governability, a lack of trust and mutual understanding, the structure of the criminal justice system, the structure of the market for corporate investigations, the use of pre-existing contacts and laws and regulations. This study furthermore suggests that the internal context of the crime may enhance the role of three of these impeding factors: trust may be more difficult to obtain in this context and reasons connected to the structuring of both the criminal justice system and the market for corporate investigations may raise the barriers for cooperation even further than in the case of external crime. Based on the results of this study, a case is made to look beyond the vertical/horizontal conceptual divide used in much (criminological) literature. Rather, public-private relationships can be conceptualised as ‘living apart together’: public and private parties independently attempt to combat internal financial crime, but also manage to find each other when deemed necessary.